Using teaching case studies for management research - Ambrosini, Veronique; Bowman, Cliff; Collier, Nardine (Sage Publications, 2010)
Teaching case studies are widely deployed in business schools. They are contextually rich in detail, and students learn by applying and adapting theoretical concepts to specific business situations described in the case. This article proposes a new way to use teaching case studies, as research materials for academics. The article addresses three questions: (1) Can teaching cases be used as an alternative to field research? (2) When can teaching case studies be used as secondary data? and (3) How can teaching case studies be used as secondary data? The article concludes that teaching case studies are an unexploited and readily available source of research data, a source which should be considered when going into the field and gathering primary data is not possible.